Early warning indicators for systemic banking crises: household debt and property prices - Khairunnisa Abd Samad,; Siti Nurazira Mohd Daud,; Nuradli Ridzwan Shah Mohd Dali, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The 2008 financial crisis was the result of escalating house prices and a hasty increase in household debt. In a sample of 41 advanced and emerging countries, this paper employs a logit estimation model to examine the role of household debt and house price as indicators of systemic banking for the period of 1980 until 2018. The results confirm that a high growth in household debt and house price increase enhances the probability for crises to erupt. While this is a consistent evidence for advanced economies, an observation of emerging economies suggests that only a change in household debt and not a change in house prices may cause banking crises to erupt. Policymakers can thus design predictive EWS models based on the surge in household debt and house prices prior to the crises which would lessen, if not alleviate, the effect of upcoming economic shocks by monitoring the macroeconomic changes.